Philosophers: Academic Professionals or Wisdom-Loving Sages? - Leonard Waks (Eidos. A Journal for Philosophy of Culture, 2024)
Preview: In July 2023 a group of philosophers gathered in Lisbon to address the boundaries, crossroads, and deadlocks in philosophy as a way of life (PWL). This short paper, based on my Lisbon talk, addresses all three topics. First, I want to highlight the boundary separating the university from everyday life. I offer a distinction between philosophers as academic professionals – university-based scholars – and philosophers as lovers of wisdom, life-guiding sages offering intelligent instruction concerning problems of living. Academic philosophers typically address fellow scholars and university students. By contrast, philosophical sages have audiences composed largely of non-philosophy professionals, including interested – and often spiritually ill – people from all walks of life. My question is: does academia set a boundary for PWL that excludes philosophers as life-guiding sages as teachers and scholars? And does this boundary create a roadblock in the development of PWL?